Potent Antioxidative and UVB Protective Effect of Water Extract of Eclipta prostrata L. - Chin-Feng Chan; Wen-Ying Huang; Hong-Yi Guo; Bo Rong Wang (The Scientific World Journal)
Oxidative stress, including Ultraviolet (UV) irradiation-induced skin damage, is involved in numerous diseases. This study demonstrates that water extract of Eclipta prostrata L. (WEP) has a potent effect in scavenging 1,1-diphenyl-2-picrylhydrazyl (DPPH), superoxide radicals, and chelating ferrous ion, exhibiting IC50 values of 0.23 mg/mL, 0.48 mg/mL, and 1.25 mg/mL, respectively. The WEP total phenol content was 176.45 mg gallic acid equivalents (GAE)/g sample. Chlorogenic acid, a component of the plant's active ingredients, was determined by HPLC and antioxidative assay. However, no caffeic acid, stigmasterol, or wedelolactone was present in WEP. WEP absorbs both UVA and UVB irradiation, and furthermore, the extract shows a dose-dependent response in the protection of HaCaT human keratinocytes and mouse fibroblasts 3T3 cells against UVB-induced cytotoxicity, which may result from a synergistic effect between chlorogenic acid and other active components present in WEP.